POTENSI PENGEMBANGAN TERNAK KERBAU DENGAN POLA PEMELIHARAAN CROP UVESTOCK SYSTEM DI PROPINSI RIAU - Yayu Zurriyati dan; Dwi Sisri Yenni (State Islamic University of Sultan Syarif Kasim Riau, 2007)
Buffalo (Bubalus hubaUs) is the one potential supplier for red meat. But, it contribution was lower than the cattle meat. The most population of buffa10 in Riau Province is at Kampar Regency. Generally, people at Kampar Regency COll8ume the buffalo milk, as IIdadih